“La ley Orgánica para la justicia laboral y reconocimiento del trabajo en el hogar; en los beneficios de orden social de los trabajadores en la ciudad de Riobamba en el periodo abril del 2015 a abril del 2016” - Torres Novillo, Natalia (2017)
The present research work offers the reader a topic not much discussed in the Legislative area and that part of a problem that affects the labor rights of the workers this is when talking about labor justice and the new reforms to the Law that violates all the benefits Are of vital importance since this practice is used by certain employers as a way to not pay their workers what they are required by law when talking about the benefits of social order, which is evidenced in many ways being the More common the non-affiliation to social security since it is an accurate proof that they are not under labor dependency and this way also does not cancel the fair remunerations as it typifies the law being always the lesser payment op to even not Payments are canceled in full. Since all these issues were addressed in the new constitutional framework established in 2008 in Montecristi in its art 328 that says that the salaries will be fair with a living wage and that advances at least to cover the basic needs of the worker as well as the His family and this will be unassignable, except in alimony, the payments must be within the agreed term between the parties and in this way to be able to enjoy all the benefits such as those of social order. Unfortunately in practice does not have a clear framework to be sanctioned is why it seeks to be punished in a clear and objective so that this right is not violated as are the benefits of social order as they benefit in the environment Social, health and family welfare.